Antecedents and Consequences of Tourist Visit Intention at Smart Tourist Destinations - Panggabean, Gideon Yosep Partogi; Risqiani, Renny (Majapahit Journal of Islamic Finance and Management, 2025)
Tourist destinations require the use of digital technology or smart tourism destinations for optimization so that they can provide convenience for tourists. However, there are several destinations that have not implemented the smart tourism destination concept due to blank spots and telecommunication signal problems. In addition, there has been a decline in tourists, especially domestic tourists, in several points in Indonesia, one of which is in Papua and Labuan Bajo. The data used in this study is primary data sourced from the results of filling out a questionnaire via Google Form. The research sample was selected using a purposive sampling method. Data analysis used for hypothesis testing is structural equation modeling (SEM) analysis. The results of the study indicate that E-Attitude, Perceived Environmental Sustainability, and Destination Image have a positive effect on Smart Tourism Destinations Visit Intentions. The results also show that Smart Tourism Destinations Visit Intentions have a positive effect on Smart Tourism Destinations Visiting Behavior. However, resource efficiency norms and tourist-perceived value do not affect smart tourism destinations' visit intentions. The results of this study provide information that companies also need to be proactive in responding to various issues related to changes in the technological superiority of tourist destinations and the need for equitable development of tourism technology throughout Indonesia.